CHANGES IN QUANTITATIVE AND QUALITATIVE PROPERTIES OF ORAL LIQUID DURING REPLACEMENT OF DENTAL DEFECTS IN PATIENTS WITH ISCHEMIC HEART DISEASE - N.O. Riabushko (Український стоматологічний альманах, 2020)
Abstract. In recent years, the attention of scientists to the study of the unique properties of saliva and related diagnostic capabilities has increased significantly. Many data on the function and composition of oral fluid in healthy people and in various somatic pathologies.